Window, Neville House - Ghosh, Ayan (2023)
Neville House is a prominent corner building at the intersection of R Kamani Road and Currimbhoy Road. The building is made from yellowish brown regular dressed stone. The ground floor has semi-circular arches with prominent imposts and ornamental keystones.